Lessons from 90 consecutive laparoscopic dismembered pyeloplasties in a residency program. (August 2012) - Arap, Marco Antonio; Torricelli, Fabio Cesar Miranda; Mitre, Anuar Ibrahim; Chambo, Jose Luis; Duarte, Ricardo Jordão; Srougi, Miguel
Abstract Objective. The aim of this study was to report on the safety and efficacy of 90 consecutive laparoscopic pyeloplasties carried out in a university hospital. Material and methods. The outcomes of 90 transperitoneal dismembered pyeloplasties that were performed by residents at the hospital from March 2004 to March 2010 were analyzed. All of the surgeries were performed because of symptomatic ureteropelvic junction obstruction. The laparoscopic Anderson–Hynes dismembered technique was used in all cases, and a double-J stent was routinely placed and left in place for 4 weeks. The patients were followed up clinically and with imaging studies. Clinical data, outcomes and complication rates for the patients were retrospectively reviewed using a prospectively maintained database. Results.The mean patient age was 38.9 (10–80) years, and 46 patients (51.1%) were males. The mean operative time was 222.5 (125–400) min. The surgery was completed laparoscopically in 96.6% of cases (87 patients). Conversion was required owing to technical difficulties in three cases. Overall, four (4.4%) patients had major complications. Seventy-six of the 87 patients (87.3%) presented improvements in symptomatology at a median follow-up of 39.7 (6–75) months. Conclusion. Laparoscopic pyeloplasty is feasible and associated with high success and low complication rates, even in a residency program.